The Meaning And Symbolic Of Campursari Kelayung Layung: An Approach To Rolland Barthes’ Semiotics - Suyatno Suyatno; Tri Pujiati (FKIP, Universitas Palangka Raya, 2023)
. Religious value is a cultural value that is passed from generation to generation to form a national character value. Religious values ​​as a cultural value can not only be seen in religious rituals, but can also be seen in campursari song. This research is conducted to find out the meaning and symbolic on tembang campursari. This research using a qualitative descriptive approach with Roland Barthes semiotic perspective. Data is collected by using documentation collection techniques on the song Campursari entitled Kelayung Layung by Deny Caknan. The results of the analysis indicate that (1) in the meaning of the denotations, connotations, and myths contained in the song Campursari Kelayung Layung has the meaning that humans as God’s creatures cry a lot for fear of death. In fact, as a human being, we must be aware that death will definitely come, but we never know when death will come.; (2) The symbolic meaning of the song Kelayung Layung has a meaning about the symbol of death. Humans die have no meaning anymore, both rank, degree, and wealth. Implication of this research shows that humans have to be aware about death.